The Relationship Between Platelet-to-Lymphocyte Ratio (PLR) and HCV RNA Levels in HCV-HIV Coinfected Patients Before and After Receiving Direct-Acting Antiviral (DAA) Therapy at Dr. Mohammad Hoesin Hospital Palembang - Tiara Anggita Qurilmi; Suyata; Harun Hudari; Masagus Irsan Saleh (International Journal of Science and Society, 2023)
The background described in the introduction section highlights the importance of studying the correlation between the platelet-to-lymphocyte ratio (PLR) and HCV RNA levels in these patients. This research follows an analytical correlational observational design with a cross-sectional approach. The study was conducted at the Internal Medicine Polyclinic of Dr. Mohammad Hoesin Hospital, Palembang. It involved 38 subjects who met the inclusion and exclusion criteria. The primary objective was to determine the correlation between PLR and HCV RNA levels in HIV-HCV coinfected patients receiving DAA therapy. The research findings concluded that there was a decrease in PLR and HCV RNA Viral Load levels in HIV-HCV coinfected patients after receiving DAA therapy compared to before receiving DAA therapy. The Platelet-to-Lymphocyte Ratio (PLR) was directly proportional to the quantitative HCV RNA Viral Load levels in HIV-HCV coinfected patients with a strong correlation value both before and after DAA therapy.